2019
DOI: 10.1039/c9ra05496k
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical properties of yttrium on W and Pb electrodes in LiCl–KCl eutectic melts

Abstract: Cyclic voltammetry, square wave voltammetry, linear polarization, chronopotentiometry and chronoamperometry were performed to investigate the electrochemical properties of Y(iii) on W and Pb electrodes in LiCl–KCl eutectic melts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…Exchange current density, a function of the reaction dynamic parameter, represents the absolute rate of oxidation and reduction reactions at its equilibrium potential . Under the assumption that there is no material transfer effect, the Butler–Volmer equation is derived to describe the relationship between net current and overpotential, as follows: Assuming that the overpotential is very small (|η| ≤ 15 mV), the exponential term in formula is simplified by Maclaurin’s series as shown in formula .…”
Section: Resultsmentioning
confidence: 99%
“…Exchange current density, a function of the reaction dynamic parameter, represents the absolute rate of oxidation and reduction reactions at its equilibrium potential . Under the assumption that there is no material transfer effect, the Butler–Volmer equation is derived to describe the relationship between net current and overpotential, as follows: Assuming that the overpotential is very small (|η| ≤ 15 mV), the exponential term in formula is simplified by Maclaurin’s series as shown in formula .…”
Section: Resultsmentioning
confidence: 99%
“…It is clear that the reduction peak potential of Dy(III) is almost constant as the frequency varies, indicating that the electrode reaction is reversible. In the inset, the peak current is a good linear relationship with the square root of frequency, demonstrating that the deposition of Dy(III) on liquid Zn electrode is controlled by diffusion, and equation can be used to calculate the diffusion coefficient: [ 45,52,53 ] Ip=nFAC01σ1+σitalicDνπ0.75emσ=exp()nFEsw2RT where E sw is the amplitude of SWV (V) and the other physical quantities have the same meaning as mentioned earlier.…”
Section: Resultsmentioning
confidence: 86%
“…A spectral pure graphite rod and Ag/Ag + were used as the auxiliary electrode and reference electrode, respectively, and the preparation process was followed as in a previous article. [ 45 ] The working electrode was W or Zn metal. Liquid Zn electrode was prepared by adding some Zn particles into an alumina crucible (1.00 cm in height and 1.50 cm in inner diameter), and W wire sheathed in an alumina tube was inserted into the crucible as a conductor.…”
Section: Methodsmentioning
confidence: 99%
“…27,28 Therefore, it is critical to recover and separate lanthanides from molten salt for nuclear fuel cycle and the purification of waste salts. 29 In recent years, the electrorecovery lanthanides from molten salt were explored on various electrodes, for example, Mg, 30 Al, [31][32][33][34] Ni, 35,36 Cu, [37][38][39] Bi, [40][41][42][43] Zn, 38,39,44,45 Cd, 46,47 Sn, 48 Pb, [49][50][51] and Ga. 52 Since there are some advantages to use low melting point metal as a liquid working electrode, many researchers paid more attentions to the electrochemical extraction using a liquid electrode. Our group investigated the electroextraction of Tb and Y from molten chloride using solid Cu and liquid Zn as working electrodes and found that under same conditions, metallic Y and Tb easily deposited on liquid Zn electrode.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is critical to recover and separate lanthanides from molten salt for nuclear fuel cycle and the purification of waste salts 29 . In recent years, the electrorecovery lanthanides from molten salt were explored on various electrodes, 30‐51 for example, Mg, 30 Al, 31‐34 Ni, 35,36 Cu, 37‐39 Bi, 40‐43 Zn, 38,39,44,45 Cd, 46,47 Sn, 48 Pb, 49‐51 and Ga 52 . Since there are some advantages to use low melting point metal as a liquid working electrode, many researchers paid more attentions to the electrochemical extraction using a liquid electrode.…”
Section: Introductionmentioning
confidence: 99%